Dynamics of social–ecological changes in a lagoon fishery in southern Brazil - Seixas, Cristiana S.; Berkes, Fikret (Navigating Social-Ecological Systems, 2001)
IntroductionAny resource management system has two interrelated dimensions: the social system and the ecological system. These dimensions are often treated separately. In the last decades, considering the failure of many conventional resource management systems (Ludwig, Hilborn, and Walters, 1993), some researchers have started investigating the dynamics of integrated social and ecological systems (henceforth social–ecological systems) in order to improve resource management (Gunderson, Holling, and Light, 1995; Berkes and Folke, 1998). To analyze the dynamics of social–ecological systems, we use common-property theory and adaptive management.The development of common-property theory (McCay and Acheson, 1987; Berkes, 1989; Ostrom, 1990; Bromley, 1992) has provided key tools for the understanding of the social dimension of management systems. A common-property (or common-pool) resource (defined as a class of resources for which exclusion is difficult and joint use involves subtractability) can be managed under four ‘pure’ property rights regimes: communal property (community-based management), state property, private property, or open access (lack of a property rights regime). In reality, many resources are managed under various mixes of these regimes, as in co-management characterized by a sharing of responsibility between the government and user groups for resource management. The degree of participation of government agencies and user groups in the decision-making process may vary greatly from one co-management case to another (McCay and Jentoft, 1996; Pomeroy and Berkes, 1997).